PHONETIC DIFFICULTIES OF THE RUSSIAN LANGUAGE (Bulletin of Innovative Research, 2026)
The article examines the phonetic difficulties of the Russian language as a systemic linguistic phenomenon caused by the peculiarities of the sound organization of speech. The analysis covers the main problematic areas of the Russian language's phonetic system, including vowel reduction, specific word stress, opposition of hard and soft consonants, assimilative processes, orthoepic norms, and intonational design of speech. Particular attention is paid to the analysis of typical phonetic errors and their impact on the communicative effectiveness of speech. The works of representatives of the Russian phonetic school, as well as modern approaches to the study of the sound aspect of language, served as the theoretical basis for the research. The article emphasizes the need for a comprehensive approach to researching and overcoming phonetic difficulties, taking into account the prospects for developing multilingual education and intercultural communication.